Robust Fabrication of Fluorescent Cellulosic Materials via Hantzsch Reaction. Issue 6 (16th November 2020) - Wang, Ruochun; Sun, Siwen; Wang, Bijia; Mao, Zhiping; Xu, Hong; Feng, Xueling; Sui, Xiaofeng
Abstract: Hantzsch reaction is one of the typical multicomponent reactions (MCRs), and it is employed herein to endow cellulosic materials with fluorescent properties. For example, acetoacetyl (ACAC)‐bearing cotton fabric prepared via transesterification with tert ‐butyl acetoacetate is subjected to an aqueous Hantzsch reaction with formaldehyde and ammonium acetate at ambient temperature. A strong fluorescent emission around 460 nm is achieved within 10 min. XPS, fluorescent spectroscopy, and elemental analysis are used to confirm the presence of 1, 4‐dihydropyridine (DHP) rings on the surface of the fabric. TGA, SEM, XRD, and mechanical testing results show that the modification process has minimum impact on intrinsic properties of the fabric. The strategy is also shown to be generally applicable to various forms of cellulosic materials and different aldehydes. This fast and simple approach enriches the application of MCR in modification of cellulose and cellulose derivatives. Abstract : Hantzsch reaction is employed for fabricating fluorescent cellulosic materials. A strong fluorescent emission around 460 nm can be achieved within 10 min at ambient temperature. The modification process hardly affects the intrinsic properties of cellulosic materials. This method is also shown to be generally applicable to various forms of cellulosic materials and different aldehydes.